A LIVING CLAIM AS AN ALTERNATIVE TO SOLVING DIVORCE CASE IN THE BOJONEGORO - Abdul Qodir; Hardian Iskandar; Dodi Jaya Wardana (EQUALEGUM International Law Journal, 2023)
Background. Maintenance is one of the husband's obligations towards his wife, and if the husband does not want to provide for his wife's children when in fact he can according to his ability, then the wife can sue him at the Religious Court. This study aims to examine in-depth script lawsuits as an alternative settlement of divorce cases in Religious Courts, as well as to analyze the efforts of judges and the execution of Religious Court decisions in cases of livelihood claims. Research Method. The method used is qualitative, while the type of research used was a juridical-empirical approach. A juridical review approach, using legal rules, books, and journals related to the research problem. Findings. Claims for maintenance can stand alone without having to divorce. The judge as the case breaker always emphasizes that married couples who want to divorce cancel their intention. Therefore, if a divorce case is caused by a husband's negligence in supporting his wife and children, then a wife can file a claim for maintenance to the Court. So, claims for a living can be a solution to the occurrence of a divorce. Conclusion. A claim for a living can be filed by bringing evidence of a lawsuit in the form of reasons why the wife sues her husband, accompanied by written documents such as a marriage certificate and husband's salary slip, and the amount of maintenance that must be given to his wife's children according to his ability.